Equine Colic Syndrome Induced by the Ingestion of Sugarcane - Albuquerque, Celina Vieira de; Lima, Leonardo Rodrigues de; Cruz, Vinicius Alves; Silva, Vinicius Pimentel; Coelho, Cássia Maria Molinaro; Souza, Bruno Gonçalves de; Freitas, Marina Sereno de; Botteon, Paulo de Tarso Landgraf (Acta Scientiae Veterinariae, 2022)
Background: Equine colic syndrome comprises numerous conditions associated with abdominal pain in horses. Impaction, a common cause of this manifestation, is strongly related to these animals’ diet. Highly fibrous diets such as sugarcane can predispose horses to colic. The clinical condition can be worsened by fermentative processes, which lead to dysbiosis, circulatory disorders and even endotoxemia. The aim of this study was to report 4 cases of colic syndrome among 8 horses that underwent an experiment to adapt them to a sugarcane-based diet, and to correlate the animals’ clinical conditions to the forage they ingested. Cases: Eight male castrated Mangalarga Marchador horses, between 5.5 and 7 years old, were subjected to an experiment to test the feasibility of sugarcane as forage. Four of these horses were taken to the Large Animal Veterinary Hospital (HVGA) of the Federal Rural University of Rio de Janeiro for treatment of abdominal signs of discomfort a few days after the exclusive consumption of sugarcane, in a proportion of 1.75% of live weight in dry matter. The animals’ symptoms ranged from behavioral signs indicative of pain to changes in vital parameters and structure of the feces, as well as changes revealed by transrectal palpation. Three of the 4 cases presented impaction in the small colon, and 1 of the horses also presented impaction in the right dorsal colon and rostral displacement of the pelvic flexure, with accumulation of contents in the right ventral colon and sternal flexure. Two of the cases were treated medically, while the other 2 required surgical intervention. The clinical condition of all the patients evolved favorably and they were discharged between 2 and 18 days. Discussion: Colic originating in the digestive system is a syndrome strongly associated with management, especially with respect to confinement, nutrition, and parasite control. During the experiment, 4 of the 8 horses fed with sugarcane presented with colic syndrome. The low quality of sugarcane fiber is due to the high degree of lignification of the plant cell wall, which favors accumulation of ingesta. The poor digestibility and sweet taste of this roughage favor increased consumption. Furthermore, its high sucrose content, associated with an increased rate of passage in the small intestine, alters the intestinal microbiome, and hence, the fermentation byproducts and pH of the ingesta. High intestinal content, allied to longer retention times in the colon and activation of the renin-angiotensin-aldosterone system, promote greater dryness of the ingesta, predisposing the occurrence of impactions in the most distal portion of the large intestine. Intestinal distension and mesenteric traction caused by the accumulation of contents and gases trigger pain, which can worsen due to displacement of the large colon. Small colon impaction, which is easily identified by transrectal palpation, evolves gradually and its treatment, both clinical and surgical, tends to have a favorable prognosis. The need for alternative food sources for horses is a growing demand; however, sugarcane as an exclusive roughage has been shown to be unsafe for horses. The low quality of the fiber and the high sucrose content of this forage can alter the digestive physiology of horses through changes in the passage rate, microbiome and motility of digesta, predisposing them to intestinal dysfunction, ingesta compaction and displacement of the large colon. Keywords: horse, acute abdomen, nutrition, diet, forage, digestibility, gastrointestinal disease. Título: Síndrome cólica em equinos induzida por ingestão de cana de açúcar. Descritores: cavalo, abdômen agudo, nutrição, dieta, foragem, digestibilidade, doença gastrointestinal.